(untitled) - Edwards, John (Hoboken, N.J., 2005)
Although telecom companies are battling for survival, technology is moving forward. In research laboratories around the world, powerful new technologies are being developed that will shape tomorrow's communications world. Telecosmos will look at the many different telecom concepts that will be adopted by both consumers and businesses in the years ahead.
Keywords: Telecommunication,Electronic apparatus and appliances,Viễn thông,Thiết bị điện tử; Technological innovations,Technological innovations,Đổi mới công nghệ,Đổi mới công nghệ